Synthesis and Characterization of Oxime-Phosphazenes Containing 2,2?-Dioxybiphenyl Groups - Cil, Erol; Turan, Gulsen; Arslan, Mustafa (Slovensko Kemijsko Drustvo, 2008)
2,2-Dichloro-4,4,6,6-bis[spiro(2', 2''-dioxy-1', 1''-biphenylyl] cyclotriphosphazene (2) was obtained from the reaction of hexachlorocyclotriphosphazene (1) with biphenyl-2,2'-diol. 2,2-Bis(4-acetylphenoxy)-4,4,6,6-bis[spiro(2', 2''dioxy- 1', 1''-biphenylyl] cyclotriphosphazene (3) was synthesized from the reaction of 2 with 4-hydroxyacetophenone. The novel oxime-cyclophosphazene containing 2,2'-dioxybiphenyl groups 4 was synthesized from the reaction of 3 with hydroxylamine hydrochloride in pyridine. The reactions of this oxime-cyclophosphazene with methyl iodide, benzyl chloride, acetyl chloride, benzoyl chloride, 4-methoxybenzoyl chloride, chloroacetyl chloride, propanoyl chloride, 2-bromoethanol and 2-chlorobenzoyl chloride were studied. Disubstituted compounds were obtained from the reactions of 4 with methyl iodide, benzyl chloride, acetyl chloride, benzoyl chloride and 4-methoxybenzoyl chloride. Pure and defined products could not be obtained from the reaction of 4 with chloroacetyl chloride, propanoyl chloride, 2-bromoethanol and 2-chlorobenzoyl chloride. All products were generally obtained in high yields. The structures of the compounds were proved by elemental analysis, IR, H-1, C-13 and P-31 NMR spectroscopy.
Keywords: Hexachlorocyclotriphosphazene; phosphazene; oxime derivatives; oxime-phosphazenes